Bioequivalence of lamotrigine 50-mg tablets in healthy male volunteers: A randomized, single-dose, 2-period, 2-sequence crossover study - Perez Lloret, Santiago (2012)
Objective: To compare the bioavailability of two 50-mg lamotrigine dispersible tablet formulations (Epilepax®, Ivax-TEVA Argentina Laboratories, Argentina, as a test formulation, and Lamictal®, GlaxoSmithKline, UK, as a reference formulation) in 24 healthy male volunteers. Material and Methods: This study was a randomized, 2-period, 2-sequence crossover design that was open for subjects and investigators, but blind for the bioanalytical lab. Serum samples were obtained over a 120-h interval. A 9-day wash-out period was allowed between treatments. The concentrations of lamotrigine were analyzed by high-performance liquid chromatography followed by ultraviolet-visible detection. Lamotrigine time-concentrations curves were obtained and the following pharmacokinetic parameters were calculated: AUC 0-t, AUC0-inf and Cmax. Bioequivalence was declared if the 90% confidence interval (CI) of the mean test/reference ratios for AUC 0-t, AUC0-inf and Cmax were within 80.00-125.00%. Results: The geometric mean and respective 90% CI of test/reference percent ratios were 100.83% (92.53-107.88%) for AUC0-t, 99.91% (93.79-108.40%) for AUC0-inf, and 95.62% (90.91-100.57%) for Cmax. No serious adverse events were observed. 1 patient reported a mild rash following the administration of each formulation. Conclusion: This single dose study found that the test and reference products met the regulatory criteria for bioequivalence in this sample of fasting healthy volunteers. These results suggest that bioequivalence studies evaluating 50-mg doses of Lamotrigine are feasible and recommended, since such doses may minimize the risk of severe rash or Stevens-Johnson Syndrome. This study was registered at the Argentinean Clinical Trials National Registry (www.anmat.gov.ar), No 1666/2008.